Presuppositions of source and receptor - Du Toit, H. C. (Neotestamentica, 1984)
In this paper presuppositions of the source and receptor in the communicative event are discussed. The point of view taken is that presupposition less exegesis is impossible and that exegesis, like any act of understanding, is constantly modified by one's own framework of ideas, beliefs and so forth. Some kinds of presuppositions are discussed and examples are adduced to show how these can influence interpretation and have found their way into translations of the Bible. Finally, the role of the exegete in general and the translator in particular, with respect to presuppositions, is discussed.